2020
DOI: 10.34172/ijtmgh.2020.09
|View full text |Cite
|
Sign up to set email alerts
|

"I Was Scared I Might Die Alone": A Qualitative Study on the Physiological and Psychological Experience of COVID-19 Survivors and the Quality of Care Received at Health Facilities

Abstract: Introduction: Although several coronavirus disease 19 (COVID-19) studies have focused on the biomedical and epidemiological manifestations of the COVID-19 virus, there is a dearth of studies that have reported the experiences of COVID-19 survivors. This study investigated the physiological and psychological experiences of COVID-19 survivors and the quality of care that they received during their recovery processes. Methods: A phenomenological approach and a purposive sampling technique were employed to select … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 20 publications
2
26
0
4
Order By: Relevance
“…From other peer-reviewed studies and this study, easy fatigability was a consistently identified symptom in COVID-19 survivors [11][12][13][14][15]. Further, several studies have identified chronic pain and psychological distress (anxiety, depression, and post-traumatic stress) in COVID-19 survivors [18][19][20][21]. This underscores the importance of channelling resources to the long-term follow-up and care of COVID-19 survivors to support their return to a normal state of health.…”
Section: Discussionmentioning
confidence: 71%
“…From other peer-reviewed studies and this study, easy fatigability was a consistently identified symptom in COVID-19 survivors [11][12][13][14][15]. Further, several studies have identified chronic pain and psychological distress (anxiety, depression, and post-traumatic stress) in COVID-19 survivors [18][19][20][21]. This underscores the importance of channelling resources to the long-term follow-up and care of COVID-19 survivors to support their return to a normal state of health.…”
Section: Discussionmentioning
confidence: 71%
“…77 Also, sufficient funds should be allocated to research 78 and training of health professionals for effective handling of epidemics. 79 …”
Section: Way Forward For Low- and Middle-income Countries (Lmics)mentioning
confidence: 99%
“…Additionally, there should be structured mental health support for this population as they at higher risk of mental illness during a pandemic. 34 Furthermore, health workers represent a crucial vulnerable demographic due to repeated exposure to sick persons, especially where personal protective equipment supplies are limited. National governments must prioritise their protection and care by investing significant portions of donor funding to not only providing medical supplies, but also supporting their families.…”
Section: Focusing On Vulnerable Communitiesmentioning
confidence: 99%
“…The existing social structures in communities can be leveraged to ensure that people get the resources or care they need while minimising the risk of infection. Additionally, there should be structured mental health support for this population as they at higher risk of mental illness during a pandemic 34 . Furthermore, health workers represent a crucial vulnerable demographic due to repeated exposure to sick persons, especially where personal protective equipment supplies are limited.…”
Section: Lessons Learnt From Hiv/aids Response and Recommendationsmentioning
confidence: 99%